2022
DOI: 10.37934/cfdl.14.8.111
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of H-Darrieus Turbine as a Rotor for Gravitational Vortex Turbine

Abstract: The main objetive of this study is to compare numerically the torque generated at 50, 75, 100, and 125 rpm by H-Darrieus turbine as a rotor for Gravitational Vortex Turbine. The rotational flow into the gravitational vortex turbine tank helped to decrease the negative torque in H-Darrieus rotor. The study was developed in ANSYS® CFX, where the model was configured at constant operating conditions. The highest torque was 0.117 Nm at 50 rpm, and the torque decreased with increasing rpm. The H-Darrieus works with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Three-dimensional numerical simulations of a Lucid spherical rotor were performed using Ansys Fluent 17.0. This commercial code solves the Navier-Stokes equations using a finite volume discretization method [17,18].…”
Section: Computation Domains and Boundary Conditionsmentioning
confidence: 99%
“…Three-dimensional numerical simulations of a Lucid spherical rotor were performed using Ansys Fluent 17.0. This commercial code solves the Navier-Stokes equations using a finite volume discretization method [17,18].…”
Section: Computation Domains and Boundary Conditionsmentioning
confidence: 99%
“…In addition, Aziz et al, [9] conducted an experimental study using a flat turbine in the enclosed gravitational water vortex system and found a maximum mechanical efficiency of 16.06% with the best efficient point at 6.3 L/s of water flow rate. Whilst Del Rio et al, [10] numerically study the torque produced at different rotational speeds and in this case, the H-Darrieus type of turbine was used as the rotor in the water vortex turbine, and they found that the maximum torque was at 50 RPM. Moreover, Aziz et al, [11] found that the maximum torque of 15.31 N can be produced using 12 runner blades at 90 o blade angle.…”
Section: Introductionmentioning
confidence: 99%